Does a joint United Nations microfinance ‘plus’ program empower female farmers in rural Ethiopia? Evidence using the pro-WEAI - Hillesland, Marya; Kaaria, Susan; Mane, Erdgin; Alemu, Mihret; Slavchevska, Vanya (Elsevier, 2022)
Microfinance is thought to be an effective tool for empowering women. Yet, previous studies that evaluate microfinance programs have mixed findings. This is in part because there are large variations in the interventions that are evaluated, but also that there is not a standardized metric of empowerment that is implemented consistently throughout the literature. This study investigates the effectiveness of a joint United Nations program aimed at empowering rural women through women-run rural savings and credit cooperatives in Oromia, Ethiopia, using the project-Women’s Empowerment in Agricultural Index. Building on more than a decade of studies and validation of different versions of the Women’s Empowerment in Agricultural Index, the tool aims to provide a standardized and comparable metric of women’s empowerment that is flexible enough to measure impacts of development projects. This study finds that the program had a positive impact on intrinsic agency for the beneficiaries with continued access to credit through the RUSACCOs between the baseline and endline. For this group of beneficiaries, the program seemed to increase the trust and respect between spouses. There is a second group of beneficiaries that appeared to have dropped out at the initial stages of the program or lost access to credit, suggesting there may have been problems with the program or possible resistance by spouses or community members. The study expands our understanding of how to measure women’s empowerment impacts of development projects within the context of a smallholder agricultural households.